Design and Feasibility of the South American Integration - Cimadamore, Alberto D. (2016)
This article analyzes two main subjects crucial for the construction of UNASUR: the need to evaluate the adecuacy between means and ends in the design of UNASUR’s institutions, and the implications that this theoretical debate would have for the viability of the most important political, social and economic project in the contemporary history of South America.